2017
DOI: 10.3390/ijerph14121530
|View full text |Cite
|
Sign up to set email alerts
|

Do Emotional Components of Alexithymia Mediate the Interplay between Cyberbullying Victimization and Perpetration?

Abstract: A substantial amount of research has revealed that cyberbully-victims have more emotional and behavioral problems than either cyberbullying victims or perpetrators. However, until now, little research has been conducted into the factors that contribute to the interplay between cyberbullying victimization and perpetration. The purpose of this study was to examine the relationship between cyberbullying victimization, perpetration, and two emotional components of alexithymia, namely difficulties in identifying an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…We found that all three bullying groups had higher alexithymia scores than young people who did not bully others, thus extending previous findings about associations between traditional and cyber bullies and alexithymia (Aricak & Ozbay, ; Wachs et al, ). A possible explanation is that when people cannot recognise or describe their own emotions, it may be hard to modulate emotions through cognitive processes, thus increasing their likelihood of aggression towards others.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that all three bullying groups had higher alexithymia scores than young people who did not bully others, thus extending previous findings about associations between traditional and cyber bullies and alexithymia (Aricak & Ozbay, ; Wachs et al, ). A possible explanation is that when people cannot recognise or describe their own emotions, it may be hard to modulate emotions through cognitive processes, thus increasing their likelihood of aggression towards others.…”
Section: Discussionsupporting
confidence: 89%
“…The 1,549 young people taking part were between 12 and 18 years old (mean [ M ] = 14.51; standard deviation [ SD ] = 1.68; 897 (57.9%) were female; 849 (54.8%), 422 of them girls, were from three schools in Germany, and 700 (45.2%), 475 of them girls, from one school in Thailand. Other sample characteristics are described in more detail elsewhere (Wachs et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Past research showed that age, sex, and cyberbullying perpetration is correlated with cyberbullying victimization and alexithymia (Tokunaga, 2010;Brody and Vangelisti, 2017;Wachs et al, 2017;Wachs and Wright, 2018).…”
Section: Control Variablesmentioning
confidence: 99%
“…Those who are both bullies and victims are said to experience more emotional and behavioral problems than bullies and victims [94]. In a study on 1549 adolescents from Germany and Thailand, alexithymia was noted to mediate the relationship between being both a victim and a bully.…”
Section: Potential Underlying Mechanismsmentioning
confidence: 99%